PENGARUH CURRENT RATIO DAN RETURN ON EQUITY TERHADAP RETURN SAHAM DENGAN KEBIJAKAN DIVIDEN SEBAGAI VARIABEL INTERVENING PADA SEKTOR PERTANIAN BEI - NIA ANISACHTUROHMAH (JURNAL ILMIAH EDUNOMIKA, 2021)
This study aims to determine the effect of current ratio and return on equity to stock returns with dividend policy as an intervening variable in the agricultural sector of the IDX 2015-2019 period. This type of research is a causal associative with a research method using a quantitative approach. The results obtained are that the current ratio has a positive and significant effect on the DPR, Return on equity has a negative and insignificant effect, the current ratio has a positive and significant effect on stock returns, ROE has a positive and significant effect, the DPR has a negative and significant effect, and the DPR does not. can affect CR and ROE on stock returns